Increasing The Ability to Manage Hypertension Care in The Elderly Using a Pocket Book - Ekasari, Mia Fatma; Nurhasanah, Aan; Suryati, Eros Siti; Badriah, Siti; Lestari, Puspita Hanggit; Aisy, Dzia Ulhaq Rohadatul; Pudjiati, Pudjiati; Hartini, Tien (Jurnal Keperawatan, 2024)
Family support is very influential in the success of hypertension care management through health education or information education about hypertension care, one of which is by using a pocket book containing information about hypertension care management for the elderly. The aim of the research was to determine the family's ability to manage hypertension in the elderly using a pocket book. This research uses a quasi-experimental design with a pre-test and post-test control group design approach. of 70 families selected by purposive sampling. Data was collected using a pretest in the treatment group and control group to determine the basic values ​​used to determine the influence of the independent variables. The treatment group was given intervention through the provision of pocket books; while the control group received a booklet about high blood pressure. The results of data collection were analyzed using univariate and bivariate using the t test. The results of this study found that after the intervention was implemented in the intervention group there were differences in knowledge, attitudes and skills between the intervention group and the control group. Researchers suggest using pocket books as a medium to increase the family's ability to manage hypertension in the elderly.